Assessment of Ground Water Quality in Churu District, Rajasthan - Khan, M A; Sharma, Mukesh (Annals of Arid Zone, 2016)
Ground water quality for irrigation under different hydrogeological formations in Churu District of Rajasthan has been assessed on the basis of 258 ground water samples. SAR and RSC values, deciding factors of water quality for irrigation purpose, have been worked out. The ground water is largely sodie due to medium to high SAR ranging from 0.05 to 68.11 with an average value of 16.28. About 67% of waters have SAR less than 18. Higher values of SAR generally found in Alluvium and SchistlPhyllite aquifers. Salinity in ground water is generally high, 77% samples have EC more than 3.0 dS mol. Due to high salinity the RSC is low in most of the samples and range from 0.0 to 26.0 MeL-I . About 79% of the water samples have RSC less than 2.5 MeL" I. Based on the above water quality parameters Churu District have been classified in to four sodic-saline zones CISIRI, C2SIRI, C2S2Rl and C3S3Rl for adopting soil amelioration strategies for irrigated agriculture. Key words: Ground water quality, hydrogeological formation, salinity, sodicity, alaklinity.